The relation between perceived need-supportive coaching behaviours, winning games, and team resilience: a longitudinal examination among basketball and soccer teams - Van Puyenbroeck, S.; Hermans, F.; Boen, F.; Fransen, K.; Vande Broek, G. (International Journal of Sport and Exercise Psychology, 2025)
In team resilience literature, team performance is consistently regarded as a primary outcome of resilient teams. However, empirical evidence linking team resilience to objective performance indicators such as effectively winning a game remains scarce. Drawing upon team resilience literature and Self-Determination Theory, this study firstly investigated whether team resilience predict the odds of winning. In addition, as sports teams inevitably experience common setbacks, this study examined whether athletes` perceived need-supportive and controlling coaching behaviours predict team resilience over time. This research therefore contributes to coaching literature by providing insights into how coaches could arm teams against adversities and increase their resilience. We conducted a three-wave longitudinal study with a sample of 397 basketball and soccer players, belonging to 39 distinct teams. They completed questionnaires at the beginning, middle and end of the season. Multilevel binomial logistic regressions indicated that team resilience significantly increased the odds of winning on top of athletes` perceived need-supportive and psychologically controlling coaching behaviours, which emerged as non-significant predictors. Random intercept cross-lagged panel models further revealed that perceived need-supportive coaching behaviours predicted higher levels of team resilience over time, while perceived psychologically controlling behaviours was associated with lower team resilience in the following waves. We conclude that team resilience is a clear predictor of actually winning a game. Although coaches` need-supportive or controlling behaviours do not directly predict their teams` odds of winning, it might enable them to create a resilient team capable of handling collective adversities.